Preoperative detection of Vesical Imaging‐Reporting and Data System (VI‐RADS) score 5 reliably identifies extravesical extension of urothelial carcinoma of the urinary bladder and predicts significant delayed time to cystectomy: time to reconsider the need for primary deep transurethral resection of bladder tumour in cases of locally advanced disease?. (17th August 2020) - Del Giudice, Francesco; Leonardo, Costantino; Simone, Giuseppe; Pecoraro, Martina; De Berardinis, Ettore; Cipollari, Stefano; Flammia, Simone; Bicchetti, Marco; Busetto, Gian Maria; Chung, Benjamin I.; Gallucci, Michele; Catalano, Carlo; et al.
Abstract : Objectives: (I) To determine Vesical Imaging‐Reporting and Data System (VI‐RADS) score 5 accuracy in predicting locally advanced bladder cancer (BCa), so as to potentially identify those patients who could avoid the morbidity of deep transurethral resection of bladder tumour (TURBT) in favour of histological sampling‐TUR prior to radical cystectomy (RC). (II) To explore the predictive value of VI‐RADS score 5 on time‐to‐cystectomy (TTC) outcomes. Patients and Methods: We retrospectively reviewed patients' ineligible or refusing cisplatin‐based combination neoadjuvant chemotherapy who underwent multiparametric magnetic resonance imaging (mpMRI) of the bladder prior to staging TURBT followed by RC for muscle‐invasive BCa. Sensitivity, specificity, positive and negative predictive values (PPV, NPV) were calculated for VI‐RADS score 5 vs. score 2–4 cases to assess the accuracy of mpMRI for extravesical BCa detection (≥pT3). VI‐RADS score performance was assessed by receiver operating characteristics curve analysis. A Κ statistic was calculated to estimate mpMRI and pathological diagnostic agreement. The risk of delayed TTC (i.e. time from initial BCa diagnosis of >3 months) was assessed using multivariable logistic regression model. Results: A total of 149 T2–T4a, cN0–M0 patients (VI‐RADS score 5, n  = 39 vs VI‐RADS score 2–4, n  = 110) were examined. VI‐RADS score 5 demonstrated sensitivity, specificity, PPV and NPV, in detecting extravesical disease of 90.2% (95% confidence interval [CI] 84–94.3), 98.1% (95% CI 94–99.6), 94.9% (95% CI 89.6–97.6) and 96.4% (95% CI 91.6–98.6), respectively. The area under the curve was 94.2% (95% CI 88.7–99.7) and inter‐reader agreement was excellent (Κinter 0.89). The mean (SD) TTC was 4.2 (2.3) and 2.8 (1.1) months for score 5 vs 2–4, respectively ( P  < 0.001). VI‐RADS score 5 was found to independently increase risk of delayed TTC (odds ratio 2.81, 95% CI 1.20–6.62). Conclusion: The VI‐RADS is valid and reliable in differentiating patients with extravesical disease from those with muscle‐confined BCa before TURBT. Detection of VI‐RADS score 5 was found to predict significant delay in TTC independently from other clinicopathological features. In the future, higher VI‐RADS scores could potentially avoid the morbidity of extensive primary resections in favour of sampling‐TUR for histology. Further prospective, larger, and multi‐institutional trials are required to validate clinical applicability of our findings.